IMPLEMENTASI NILAI SILA KETIGA PANCASILA DALAM MENGEMBANGKAN KARAKTER KEBANGSAAN PADA TARIAN ZAPIN MELAYU DI DESA MADANG PERMAI KECAMATAN SUHAID KABUPATEN KAPUAS HULU - Mardawani, Mardawani; Juri, Juri; Anjenie, Sarah (STKIP Persada Khatulistiwa Sintang, 2023)
This research examines the implementation of the value of the third precept of Pancasila in developing national character in the preservation of Zapin Melayu in Desa Madang Permai, Kecamtan Suhaid Kabupaten Kapuas Hulu. This research uses Qualitative methods and Ethnographic research forms. Data collection techniques using direct observation techniques, interviews and documentation studies. The data collection tool uses observation sheets, interview guidelines, and documentation study guidelines. The results showed that: 1) the impelemation of the value of the third precept of pancasila in the implementation of Zapin Melayu (belangkah) in Desa Madang Permai that is: (a) Pre-Implementation of Zapin Melayu, which includes preparing the equipment used, preparing the forging of the implementation, preparation of dance members. (b) the core performance of the Malayu Zapin dance, namely the gambus player and drummer, entered the first time to the area of the Malayu Zapin dance, then the gambus players plucked the gambus and the dance members. 2) the value of national character in the preservation of Malayu Zapin includes: religious values, social care, creativity, friendship, and love of the motherland. 3) supporting factors and obstacles to the implementation of Zapin Melayu are supported by the village government and support from the community. Desa Madang Permai Kecamatan Suhaid Kabupaten Kapuas Hulu.Â Keywords: The Third Precept of Pancasila, Malayu Zapin Dance, Nationality Character.